Vibration and damping analysis of doubly curved viscoelastic-FGM sandwich shell structures using FOSDT. (August 2020) - Sahu, Nishant Kumar; Biswal, Deepak Kumar; Joseph, Shince V; Mohanty, Sukesh Chandra
Abstract: This paper deals with the free vibration study of doubly curved sandwich shell panels having a core of viscoelastic material, constrained by a Functionally Graded Material (FGM) layer. The FGM constraining layer used in this analysis is made up of Metal-Ceramic (Al/ZrO2 ) constituents with top surface being the ceramic rich and the bottom surface is rich in metal. Constrained layer damping (CLD) used for the viscoelastic core improves the damping characteristics of the sandwich shell panel. The mechanical properties of the FGM top layer is considered to vary through the thickness direction, following the Power Law distribution. The normal and shear deformations of the viscoelastic core is considered in the analysis and, the variation of the in-plane and transverse displacements of the core is assumed to be linear along the thickness direction. The base layer of the sandwich structure is made up of isotropic elastic material. The modelling is carried out using the First Order Shear Deformation Theory (FOSDT) with the help of Finite Element Analysis (FEA) by considering that, the transverse deformations of the face layers are independent of their in-plane deformations. Parametric analyses have been carried out to investigate the effect of variation of various system parameters such as power law index, aspect ratio, core thickness ratio, constraining layer thickness ratio and core loss factor on the natural frequencies and modal loss factors of the sandwich shell structure.